Feeding areas used by individual Pink-footed Geese Anser brachyrhynchus around the Loch of Strathbeg, North-East Scotland - Keller, V E; Gallo-Orsi, U; Patterson, I J; Naef-Daenzer, B (Wildfowl, 1997)
The aim of the study was to determine whether individual Pink-footed Geese had restricted feeding ranges within the whole area used by the local population, so as to assess whether refuges were likely to experience a rapid turnover. In spring 1989 and 1990 the feeding distribution of Pink-footed Geese roosting at the Loch of Strathbeg, Grampian, UK was determined by driving along a fixed transect route twice each week. Distinct core feeding areas, which remained consistent between the two years, could be identified. Mean densities of goose droppings in areas at different distances from the roost did not differ in March, but in April densities in areas far from the roost were significantly lower than those in areas close tot he roost. Tracking of radio-tagged Pinkfeet in 1990-91 showed that individual geese were not confined to particular core feeding areas, but that most used several different ones and even moved between adjacent roosts. This suggests that refuge management must take into account a rapid turnover in the individual geese using a particular site.